Balanced Scorecard for performance assessment in healthcare settings: a review of literature. (13th November 2019) - Cacciatore, P; Kannengiesser, P; Carini, E; Di Pilla, A; Pezzullo, A M; Hoxhaj, I; Gabutti, I; Cicchetti, A; Boccia, S; Specchia, M L
Abstract: Background: The Balanced-Scorecard (BSC) is a management tool developed in the early 1990s to balance the impact of financial and non-financial parameters and analyse the organisational performance in private companies according to four determinants. The original BSC has spread to different sectors in the last decades, including healthcare services, in numerous amended versions. The aim of our project was to identify potential indicators of BSC for performance evaluation in general hospitals. Methods: We performed a systematic review of literature on Pubmed and Web of Science using the search string "balanced scorecard AND healthcare AND indicators". We found 102 papers; 80 papers were removed for irrelevance, absence of full text or performance indicators. We only considered articles that followed the classic structure of BSC (Customer, Internal Processes, Financial, and Learning and Growth). The indicators listed in them were classified according to the four determinants of organisational performance. Results: Eight articles out of 22 followed the classic structure of the BSC. The most represented category was Internal Processes (59 indicators), followed by Learning and Growth (52), Customer (40) and Financial (33). The number of common/overlapping indicators was low (5 for Internal Processes and 4 for the three other categories). Conclusions: While BSC has spread to different settings, the list of indicators used in the classic four determinants for performance evaluation is heterogeneous. While common points can be identified between indicators, our review highlighted that every BSC is developed in a unique way which makes it difficult to identify a general framework adaptable to different hospital settings. Key messages: The use of the Balanced Scorecard as management tool has spread to healthcare settings in the last decade. Indicators in BSC for healthcare settings are heterogeneous and only a limited number follow the standard structure of BSC.